How does gut microbiota affect the vaginitis axis? The mediating role of plasma metabolites - Mo Li; Qianyu Zhang; Tong Wu; Lanfang Ma; Dianxing Hu; Zixuan Yuan; Shixuan Wang; Aiyue Luo; Jinjin Zhang (Microbiology Spectrum)
ABSTRACT Vaginitis is the most common problem afflicting women of childbearing age. However, the underlying etiological factors remain poorly understood, leading to recurrent vaginitis and constraining clinical management. Here, we explored whether the gut microbiota influences the risk of vaginitis by performing a two-sample Mendelian randomization analysis using the largest genome-wide association studies to date. Four gut taxa in genus levels were identified related to vaginitis: Candidatus Soleaferrea (inverse-variance weighted [IVW] odds ratio [OR] = 2.20, P = 0.026), Dialister (IVW OR = 2.62, P = 0.029), Lachnospiraceae UCG-008 (IVW OR = 0.41, P = 0.0067), and Ruminiclostridium 5 (IVW OR = 0.080, P = 1.42 × 10−5). We further explored the mediation effect of the plasma metabolites by two-step Mendelian randomization (MR) and multivariable MR. The findings indicated that 3-phosphoglycerate and lysophosphatidylcholine antagonistically act against the two identified risk factors (Candidatus Soleaferrea and Dialister, respectively) of vaginitis, thus appearing to confer protective effects against vaginitis. On the contrary, the elevation of arachidonate/pyruvate ratio and reduction in palmitate/myristate ratio mediated the protective effects of Lachnospiraceae UCG-008 against vaginitis. These findings support a potential causal role for gut microbiota in the development of vaginitis, thereby providing potential strategies for its prevention and intervention.IMPORTANCEVaginitis is the most common problem afflicting women of childbearing age. However, the underlying etiological factors remain poorly understood, leading to recurrent vaginitis and constraining clinical management. Besides, the human gut and vagina are important organs that are both colonized by thousands of microorganisms impacting human physiology and health. Whether there is an interplay between the microecosystems is intriguing and unclear. This study evaluated the potential causal relationship between the gut microbiota and vaginitis and suggested that specific types of gut microbiota may be the potential risk or protective factors of vaginitis mediated or suppressed by certain plasma metabolites. These findings provide treatment insights for vaginitis.